Hydraulic retention time and pH affect the performance and microbial communities of passive bioreactors for treatment of acid mine drainage - Aoyagi, Tomo (AMB Express, 2017)
For acceleration of removing toxic metals from acid mine drainage (AMD), the effects of hydraulic retention time (HRT) and pH on the reactor performance and microbial community structure in the depth direction of a laboratory-scale packed-bed bioreactor containing rice bran as waste organic material were investigated. The HRT was shortened stepwise from 25 to 12 h, 8 h, and 6 to 5 h under the neutral condition using AMD neutralized with limestone (pH 6.3), and from 25 to 20 h, 12 h, and 8 to 7 h under the acid condition using AMD (pH 3.0). Under the neutral condition, the bioreactor stably operated up to 6 h HRT, which was shorter than under the acid condition (up to 20 h HRT). During stable sulfate reduction, both the organic matter-remaining condition and the low oxidation–reduction potential condition in lower parts of the reactor were observed. Principal coordinate analysis of Illumina sequencing data of 16S rRNA genes revealed a dynamic transition of the microbial communities at the boundary between stable and unstable operation in response to reductions in HRT. During stable operation under both the neutral and acid conditions, several fermentative operational taxonomic units (OTUs) from the phyla Firmicutes and Bacteroidetes dominated in lower parts of the bioreactor, suggesting that co-existence of these OTUs might lead to metabolic activation of sulfate-reducing bacteria. In contrast, during unstable operation at shorter HRTs, an OTU from the candidate phylum OP11 were found under both conditions. This study demonstrated that these microorganisms can be used to monitor the treatment of AMD, which suggests stable or deteriorated performance of the system. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13568-017-0440-z) contains supplementary material, which is available to authorized users.